Exploring Digital Leadership Effectiveness: A Mixed Methods Comparative Study of Cambodian Secondary Schools - Por Vutha (JF Publisher, 2026)
This mixed methods study examined digital leadership effectiveness among secondary school principals in Phnom Penh, Kampong Cham, and Kandal provinces, Cambodia. Using an explanatory sequential design, quantitative data were collected from 385 participants including principals, vice principals, teachers, students, parents, educational administrators, policymakers, and private sector representatives through structured questionnaires employing five-point Likert scales. Qualitative data comprised semi-structured interviews exploring digital leadership practices across New Generation Schools and private secondary schools. Results revealed predominantly positive perceptions of digital leadership (M = 3.90, SD = 1.15), with highest consensus on digital collaboration and communication (M = 4.58, SD = 0.49). Reliability analysis demonstrated exceptional internal consistency for knowledge (α = 0.918), skills (α = 0.984), and attitudes (α = 1.000) constructs. However, substantial disparities emerged across school types. New Generation Schools and private institutions demonstrated advanced digital integration through systematic use of Learning Management Systems, Google Classroom, and digital communication platforms, whilst traditional public schools relied predominantly on paper-based administration due to infrastructure deficits and limited professional development access. Hypothesis testing confirmed that leadership dimensions positively influenced principals' knowledge, skills, and attitudes, which subsequently affected teacher performance and student achievement. Teacher readiness, student competence, and school culture moderated these relationships. Findings indicate that 42.1 per cent of principals lacked digital technology training, representing a critical professional development gap. The study concludes that bridging Cambodia's digital divide requires comprehensive interventions addressing infrastructure investment, mandatory digital leadership competencies in preparation programmes, sustained professional development, and supportive policy frameworks to ensure equitable educational quality across all secondary schools.